Observational and genetic evidence highlight the association of human sleep behaviors with the incidence of fracture - Yu Qian (Nature Portfolio, 2021)
Yu Qian, Jiangwei Xia, et al. perform a prospective study of the association between sleep problems and fractures, and generate a predictive sleep risk score. They report that participants with a higher sleep risk score or insomnia exhibited increased risks of fracture, and that falls had a larger intermediary effect than bone mineral density in this association.